The Role of Mental Metaphor and its Rhetorical Secrets in Arabic Language - Bacha, Syed Abdul Salam; Khan, Habibullah (Journal of Islamic and Religious Studies, 2016)
The Trope (المجاز) is one of the vital chapters in the Eloquence of Arabic Language and its Rhetoric. It has two kinds; the Linguistic Trope/figuration and the Mental Trope/ figuration. In this article I concentrated on Mental Trope and all of its concerned motives in detail with examples of Quranic Verses and Prophetic Hadiths and Arabic Poetry. I have also discussed the view point of Abd Al-Qahir Al-Jurjani and Al-Khatib- Al-Quziani about Mental Trope/ figuration and its Rhetoric mysteries. I also shed light on academic ambivalences and differences in their view points. Furthermore, I have discussed the motives of Mental Trope in the negative mode and elaborated mental/rational circumstances in the negative mode in the light of views of Abd Al-Qahir Al-Jurjani and Saad ul din Al- Taftazani. At the end of this article I have mentioned Mental Trope’s presumptions and concluded the article with best positive sequences.